“Patient-Centered” Self-Efficacy and Chronic Disease Management: Associations with Doctors’ Intentions and Perceived Treatment Effectiveness - Chi Zhou; Kaixiao Qu; Xiaoling Lin; Qunfan Huang; Zhiyu Wu; Hangyuan Gao; Yinuo Lian; Minmin Jiang; Yin Dong (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
“Patient-centered” self-efficacy enhances patient satisfaction and compliance, thereby improving the effectiveness of chronic health management. This study assesses the “patient-centered” self-efficacy of doctors in China and explores its association with their intentions and perceived treatment effectiveness in chronic disease management within county medical alliances. A cross-sectional survey was conducted among 539 doctors from 6 county-level hospitals and 18 community health centers in Zhejiang Province, China. The Self-Efficacy in Patient-Centeredness Questionnaire (SEPCQ) was used to measure doctors’ self-efficacy. The average total score of the SEPCQ in our sample was 88.28 ± 17.61. For domain scores, dealing with communicative challenges had the highest average score (3.43 ± 0.70), while sharing information and power had the lowest average score (3.38 ± 0.71). The total SEPCQ score was associated with higher odds for individuals with a monthly per capita income of 5001 to 7000 RMB (OR = 1.597, 95% CI: 1.002-2.545) and for those from the southeast area district (OR = 1.719, 95% CI: 1.131-2.615). Each domain of the SEPCQ was associated with higher odds for doctors’ intentions, perceived treatment capacity, and perceived treatment effectiveness in chronic disease management. The study finds that doctors in China have high “patient-centered” self-efficacy, which is crucial for quality health management services. Future efforts should target interventions to further elevate doctors’ self-efficacy and optimize the quality of care within county medical alliances.